Contributing factor to illegal house renovation: a house owner’s perspective / Muhamad Akmal Hakimi Zulkifli and Muhammad Zahir Zulkernain - Zulkifli, Muhamad Akmal Hakimi; Zulkernain, Muhammad Zahir (2023)
Legalhouse renovations have caused various issues for Malaysian local governments. Local authorities have borne an unjustified financial burden as a result of enforcement work, as have homeowners. As a result, the purpose of this research is to investigate the challenges connected with unlawful house renovations in a local council and to investigate the views of the local council's stakeholders to the prospect of including the community in reframing the housing remodelling rules. The finding suggests that the difficulties with unlawful renovations are mostly the result of an inadequate guideline, a lack of public knowledge, unconstrained small contractors, and cumbersome enforcement procedures. The stakeholders on the council also agreed that increased community engagement is welcomed in redesigning the existing remodelling guideline, however not to the degree of giving the general public complete control over the final output.